Understory plant species recruitment and expansion spur community shifts following forest restoration treatments - Demarest, Arièl B., author; Fornwalt, Paula J., author; Wolk, Brett H., author; Briggs, Jennifer S., author; Springer, Judith D., author; Wiley Periodicals LLC, publisher (Colorado State University. Libraries, 2025)
Restoration treatments have been implemented in many of the dry conifer forests of the western United States. By decreasing forest density and increasing forest heterogeneity, these treatments are generally effective at meeting their primary objective of reducing the risk of uncharacteristically severe wildfire. Treatments also commonly achieve a secondary objective of increasing overall native understory plant species richness and cover. However, it is less certain how treatments affect the recruitment, loss, and growth of individual understory plant species and, in turn, shape the composition of the understory plant community. We investigated these finer effects of forest restoration treatments on understory communities in the Colorado Front Range by collecting data pre-treatment and 1-2 years and 4-6 years post-treatment at 155 plots in treated and untreated areas. Treatments were implemented mechanically by cutting trees with heavy equipment or chainsaw; cut material was either removed, piled, piled and burned, scattered, or masticated. Species turnover analysis indicated that at 4-6 years post-treatment, losses of pre-treatment native species, as well as losses in the cover of pre-treatment native species, were attributable to background turnover rather than to treatment. Species turnover analysis also showed that the post-treatment recruitment of native species was greater in treated than untreated plots and that native species persisting from pre- to post-treatment contributed the most to the increased cover found in treated plots. Multivariate analysis demonstrated subtle but statistically significant differences in species composition in treated versus untreated plots after treatment. Indicator species analysis clarified which species contributed to post-treatment turnover and composition differences. No strong native or non-native indicator species were found for untreated plots at any sampling period, or for treated plots pre-treatment. However, at 4-6 years post-treatment, eight native species and two non-native species were strongly indicative of treated plots, most of which were open forest species. Based on these results, and our previous results that identified positive treatment effects on overall native cover and species richness, we conclude that mechanical forest restoration treatments benefited native understory plant communities in the Colorado Front Range both at broad and fine levels.
Keywords: Colorado; dry conifer forests; forest restoration; indicator species; species composition; species turnover; understory plants